2018
DOI: 10.1080/14686996.2018.1509275
|View full text |Cite
|
Sign up to set email alerts
|

Insights into photovoltaic properties of ternary organic solar cells from phase diagrams

Abstract: The efficiency of ternary organic solar cells relies on the spontaneous establishment of a nanostructured network of donor and acceptor phases during film formation. A fundamental understanding of phase composition and arrangement and correlations to photovoltaic device parameters is of utmost relevance for both science and technology. We demonstrate a general approach to understanding solar cell behavior from simple thermodynamic principles. For two ternary blend systems we construct and model phase diagrams.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…10,16,17 knowledge from binary systems cannot be easily transferred to the ternary devices. 16,18,19 For example, the problems of controlled crystallization and tailored compatibility of D/A materials in BHJ need to be investigated in more detail. In general, it has been widely reported that a high crystallinity in the BHJ layer is critical for a high device current because the charge mobility and even the exciton diffusion length are enhanced in crystallites.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,16,17 knowledge from binary systems cannot be easily transferred to the ternary devices. 16,18,19 For example, the problems of controlled crystallization and tailored compatibility of D/A materials in BHJ need to be investigated in more detail. In general, it has been widely reported that a high crystallinity in the BHJ layer is critical for a high device current because the charge mobility and even the exciton diffusion length are enhanced in crystallites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Alternatively, ternary OSCs formed by a blend of donor1/donor2/acceptor (D1/D2/A) or donor1/acceptor1/acceptor2 (D1/A1/A2) have attracted considerable attention because they allow us to maintain the simple craftsmanship used in binary OSCs and simultaneously expand the absorption range. ,, By moving from 2 to 3 components in the active layer, the complexity is further increased by the larger number of possible D/A partners. Fundamental knowledge from binary systems cannot be easily transferred to the ternary devices. ,, For example, the problems of controlled crystallization and tailored compatibility of D/A materials in BHJ need to be investigated in more detail. In general, it has been widely reported that a high crystallinity in the BHJ layer is critical for a high device current because the charge mobility and even the exciton diffusion length are enhanced in crystallites. , Moreover, the control of the orientation of the crystallites with respect to the electrodes is of essential importance, since charge transport is commonly anisotropic for the crystallites. , …”
Section: Introductionmentioning
confidence: 99%
“…However, the additional material may form discrete phases and thus violate the bicontinuous interpenetrating network, which acts as traps for the charge recombination. Since the intermolecular interactions in the ternary blends are more complex than the binary blends, it is much difficult to tune the morphology of ternary blends, which restricts the further performance enhancement of TSCs …”
Section: Introductionmentioning
confidence: 99%
“…Cyanine dyes have a number of interesting property characteristics such as ease of synthesis and purification, tunable absorption in a narrow wavelength range, high light extinction coefficients and good film formation properties from organic solvents. Cyanine dyes have initially been used as spectral sensitizers for silver halide emulsion photography [24], and have recently attracted interest for optoelectronic device applications such as light-emitting electrochemical cells [25], solar cells [26][27][28][29][30][31][32] and NIR photodetectors [20,33].…”
Section: Introductionmentioning
confidence: 99%